PENGARUH SISTEM INFORMASI MANAJEMEN BERBASIS KOMPUTER TERHADAP USER PERFORMANCE DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING PADA KARYAWAN PD BPR BKK KARANGANYAR - Mulyono, Erlina Sih Rahayu & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2018)
This study aims to analyze effect of computer-based Management Information Systems on user performance and analyze the effect of computer-based Management Information Systems on user performance moderated locus of control in PD BPR BKK Karanganyar. This study using sample of 64 employees (end user computing). Data analysis using regression analysis and absolute residual-test. Conclusions 1) Computer-based Management Information System has a significant effect on user performance (2) locus of control moderates the relationship between computer-based Management Information Systems on user performance. Keywords: computer-based Management Information System, locus of control, user performance